Diagnostic and Metastatic Predictive Value of Urinary Exosomal miR-26b-3p in Prostate Cancer: A Prospective Observational Study - Sufriyudi, Muhammad; Danarto, HR (Journal of Applied Nursing and Health, 2026)
Background: Prostate cancer (PCa) remains challenging to diagnose due to the limited accuracy of PSA testing. Urinary exosomal miR-26b-3p is a promising non-invasive biomarker, but evidence across PCa metastatic stages is limited, particularly in LMICs. This study evaluated miR-26b-3p expression in BPH, non-metastatic PCa, and metastatic PCa (M1b and M1c), and assessed its diagnostic and metastatic discrimination potential. Methods: This prospective, observational, single-center study was conducted at Dr Sardjito General Hospital, Yogyakarta, Indonesia, from January 2023 to December 2023, and reported in accordance with the STROBE guidelines. A total of 40 male participants (12 BPH and 28 PCa) were enrolled using consecutive sampling. Inclusion criteria were men aged ≥40 years with histopathologically confirmed BPH or PCa who provided written informed consent. Exclusion criteria were prior pelvic radiotherapy, urinary tract infection, hematuria, or incomplete urine specimens. The independent variable was the clinical diagnostic group; the dependent variable was relative urinary exosomal miR-26b-3p expression. Urinary exosomes were isolated, and miR-26b-3p was quantified by quantitative real-time PCR (qPCR). Group comparisons used one-way ANOVA with post-hoc analysis, and diagnostic performance was evaluated by Receiver Operating Characteristic (ROC) analysis with Area Under the Curve (AUC) and 95% confidence interval (CI). Results: miR-26b-3p expression differed significantly among the four groups (p = 0.002). Mean ± SD expression was 6.6 ± 3.4 in BPH, 44.2 ± 25.4 in non-metastatic PCa, 46.7 ± 41.1 in M1b PCa, and 35.1 ± 21.3 in M1c PCa. ROC analysis demonstrated excellent diagnostic performance for differentiating BPH from PCa (AUC = 0.982; 95% CI: 0.943–1.000; p < 0.001). Conclusion: Urinary exosomal miR-26b-3p shows strong diagnostic discrimination between BPH and PCa and is associated with metastatic status, supporting its potential as a non-invasive biomarker for prostate cancer screening and metastatic risk stratification. Multicenter validation in larger, ethnically diverse cohorts is needed before clinical implementation.